Fabrication of cornstarch biopolymer-derived nano porous carbon as electrode material for supercapacitor application - Nath, Gaurav; Singh, Pramod K.; Dhapola, Pawan Singh; Dohare, Sushil; Noor, I. M.; Sharma, Tejas; Singh, Abhimanyu (Springer, 2022)
Porous carbon is prepared from the cornstarch biopolymer by simple carbonization process initially at 800 °C. This carbon sample has been activated by gasification with the help of oxidizing gas and by reaction with certain chemicals for its pore development. The final product of activated carbon is then characterized by techniques like XRD, RAMAN, BET, TGA, FESEM, and EDX to study all its behavior. The results of these characterizations have been thoroughly studied in the Sect. 3. The carbon is used as an electrode material to decorate the supercapacitor electrode by 1 mg of coating. Polymer electrolyte film of PVDF-HFP doped with 300 wt% of 1-ethyl-3-methylimidazolium tricyanomethanide (TCM) (optimized for better conductivity) ionic liquid is used as a separator. A supercapacitor device is then fabricated at laboratory scale with the prepared porous carbon electrodes sandwiched with the electrolyte film which yield a specific capacitance of 188.4 F/gm at 10 mHz confirmed from the electrochemical low-frequency impedance spectroscopy plot. Cyclic voltammetry results were also measured, yielding a high specific capacitance of 184.8 F/gm at 5 mV/s.